Severe Congenital Myopathy and Neuropathy with Congenital Cataracts due to GFER Variant: A Neuropathological Study - Sanchez-Marco, Silvia Beatriz; Pierre, Germaine; Sharples, Peta; Love, Seth; Urankar, Kathryn; Hilliard, Tom; Lunt, Peter; Churchill, Amanda; Aungraheeta, Riyaad; Dallosso, Anthony; Evans, Julie; Williams, Maggie; Majumdar, Anirban (Journal of Pediatric Neurology, 2022)
We describe the clinical, muscle and nerve biopsy, and genetic findings in a 10-year-old girl with a profound and rapid global regression. She presented during neonatal period with hypotonia, followed by weakness in the facial, bulbar, respiratory, and neck flexor muscles. She developed bilateral cataracts at 4 months of age and started to regress. Quadriceps muscle biopsy revealed extensive fiber atrophy but sparing of some, predominantly type 1, fibers. Sural nerve biopsy showed depletion of myelinated and unmyelinated fibers; most remaining myelinated fibers were of small caliber. Neuroimaging revealed global brain atrophy. Although the investigations indicated a multisystem disorder, extensive genetic and metabolic investigations were negative. She was tracheostomy- and ventilator-dependent for most of her life. The child died at 10 years of age. Further deoxyribonucleic acid analysis undertaken via whole genome sequencing revealed a novel pathogenic GFER sequence variant consistent with the patient's clinical presentation.
Keywords: GFER; congenital myopathy; congenital neuropathy; cataracts; developmental delay